The orthography of the Fedorovsky II Parimeinik of the 13th century - A.O. Shtatnova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The spelling, phonetics, and grammar of the Fedorovsky II Parimeinik of the 13th century were analyzed for the first time. The results obtained were used to specify the time when the manuscript was created and the region of its origin: it should be dated to around the second half of the 13th century and confined to the corpus of texts having either Pskov or Novgorod origin. A number of examples were provided to show that the text under study is highly variable at all levels. The active usage of graphic doublets was found. It was noticed that the Old Slavonic reflexes occur along with the Old Russian ones. In the system of past tenses, both archaic and innovative forms were registered. The mobility of the norms of the Old Russian language was observed, thereby indicating the liberalization of the language of church literature. Therefore, the Fedorovsky II Parimeinik was susceptible to changes that took place in the language system of that time and fell under the influence of Russification.